The native architecture of Asir region in Saudi Arabia: stone duct towers of the highlands - al-Jawahrah, Hani Muhammad (The University of Edinburgh, 1996)
This thesis is about the native architecture of the highlands of the Asfr region in the south-western corner of Saudi Arabia. The thesis is made up of two parts. The first part introduces the region and its architecture. It has four chapters. The first chapter discusses a wide range of issues and its relationship to the architecture. The second chapter discusses significant cultural and social aspects of the people, and their impact on the architecture. The third chapter introduces the native architecture of the highlands, and classifies this architecture into towers and villages. It provides ground plans for the most important types of towers, and assigns them to their geographic and tribal context. The chapter also describes the basic features of these towers and villages. The fourth chapter describes the natural features of the highlands and their influence on selected stone-built villages.

The second part is devoted to the study of one type of tower built in the central and south sections of the highlands: the duct tower. Twelve duct towers are under close focus in this part. This part has five chapters. Chapter five classifies the duct types of these towers and explores the purpose of the duct. Chapter six describes and argues the purpose of three duct grain towers built in different physical contexts. The first tower is an isolated tower. The second tower is built inside a compact stone village. The third tower and its companions overlook a stone village. Chapter seven describes three duct defensive towers. The first tower is built inside a defended stone village. The second tower is built outside a compact village . The third tower is built within a fortress . Chapter eight describes three watch and retreat towers. The first tower is a simple duct tower. The second tower is of the platform-duct type. These two towers are built overlooking stone villages. The third tower is a round duct tower built beside grain fields. Other round towers are also discussed in this chapter. Chapter nine describes three duct residential towers. Two of these towers are built together and the third tower is isolated. Other residential towers in the south section are also discussed in this chapter.

The thesis ends with an assessment of the findings and suggests the most important conclusions that can be drawn from this research. Drawings are used intensively throughout the thesis to deliver messages that could not be accommodated in the text.